Recognizing and rewarding employees - Bowen, R. Brayton (New York : McGraw Hill, 2000)
This is a book about a new frontier-the new workplace. It's a book about the needs and interests of the new workforce-epitomized by the "free agent/employee"-and the tools of recognition and rewards.
Keywords: Employees; Employee motivation; Incentives in industry